A Person-Centered Approach to Adolescent Nonsuicidal Self-Injury: Predictors and Correlates in a Community Sample - Reinhardt, Melinda; Rice, Kenneth G.; Durán, Barbara S.; Kökönyei, Gyöngyi (Journal of youth and adolescence, 2022)
Growing incidence of nonsuicidal self-injury (NSSI) and a lack of intensive examination of NSSI variability among adolescents justify identification of latent classes based on the endorsement of different NSSI behaviors. Latent class analysis was used to detect the heterogeneity of past month NSSI among 322 high school students (73.2% female). Two interpretable latent classes emerged. The Severe/Multimethod NSSI class (39%) engaged in almost all forms of NSSI with high intensity and motivated mainly for intrapersonal reasons. The results imply that compared to Mild/Moderate NSSI group (61%), the Severe class is at greater risk for poor mental health, which can exacerbate further NSSI acts. In school settings, identifying adolescents who are vulnerable for more severe NSSI can help to interrupt NSSI trajectories to emerging adulthood.